Life cycle evaluation of an intercooled gas turbine plant used in conjunction with renewable energy - Isaiah, ThankGod E.; Dabbashi, Siddig; Bosak, Dawid; Sampath, Suresh; Di Lorenzo, Giuseppina; Pilidis, Pericles (Elsevier, 2016)
The life cycle estimation of power plants is important for gas turbine operators. With the introduction of wind energy into the grid, gas turbine operators now operate their plants in Load–Following modes as back-ups to the renewable energy sources which include wind, solar, etc. The motive behind this study is to look at how much life is consumed when an intercooled power plant with 100 MW power output is used in conjunction with wind energy. This operation causes fluctuations because the wind energy is unpredictable and overtime causes adverse effects on the life of the plant – The High Pressure Turbine Blades. Such fluctuations give rise to low cycle fatigue and creep failure of the blades depending on the operating regime used. A performance based model that is capable of estimating the life consumed of an intercooled power plant has been developed. The model has the capability of estimating the life consumed based on seasonal power demands and operations. An in-depth comparison was undertaken on the life consumed during the seasons of operation and arrives at the conclusion that during summer, the creep and low cycle life is consumed higher than the rest periods. A comparison was also made to determine the life consumed between Load–Following and stop/start operating scenarios. It was also observed that daily creep life consumption in summer was higher than the winter period in-spite of having lower average daily operating hours in a Start–Stop operating scenario.
Keywords: Gas turbines; Life cycle; Load–Following; Power demand; Renewable energy; Thermodynamic cycle; Thermal efficiency